An Experimental Evaluation of the State Adult Attachment Measure: The Influence of Attachment Primes on the Content of State Attachment Representations. Issue 2 (June 2014) - Bosmans, Guy; Bowles, David P.; Dewitte, Marieke; De Winter, Simon; Braet, Caroline
Attachment theory predicts cross-contextual stability of attachment representations, but research findings are rather mixed. Recently, it has been suggested that these mixed findings reflect the existence of both state and trait attachment components. The development of the State Adult Attachment Measure (SAAM) has enabled an investigation of this hypothesis. The current study aimed to evaluate the extent to which the SAAM is a useful instrument for studying such state attachment hypotheses. For this purpose, a two-week longitudinal study investigated whether the manipulation of the temporal accessibility of different attachment contents activates different within-person attachment representations. The impact of attachment primes before re-administering the SAAM was investigated in 268 participants. Results showed that the SAAM was meaningfully related to evaluations of self and attachment figures. Moreover, activation of different attachment contexts influenced state attachment towards partners as primary attachment figures. The results provide support for the SAAM as a measure of state attachment towards partners, but data on parent attachment were less straightforward. In all, the current study provided support for contemporary models of attachment as comprising both trait-like stability and context-dependent variability in attachment state.